Visual Auditory and Kinesthetic Learning Model to Improve Students’ Motivation, Creativity, and Learning Outcomes - Calvin Malvigie; Victor Novianto; Sharifah Zannierah Syed Marzuki (Research and Innovation in Social Science Education Journal (RISSEJ), 2023)
This study aims to identify how well the application of the VAK learning model can improve students' motivation, creativity, and scores in social science subjects. The study applies Classroom Action Research with two cycles. Each cycle consists of planning, implementing, observing, and reflecting. The respondents are 30 students of grade 9C grade at SMP N 1 Mlati which consists of 19 females and 11 males. The data analysis technique used quantitative descriptive methods. The results of the study show that applying the VAK learning model can increase the motivation, creativity, and outcomes of the students. The score of motivation of the pre-cycle is high and very high categories; as much as 43.34%, in cycle I it gets 70%, and finally, in cycle II it gets 100%. The score of creativity in the pre-cycle stage is good and very good categories; as much as 20%, the cycle I it gets 66.67%, and it gets  96.67% in cycle II. The minimum score for students in the pre-cycle stage is 46.67%, in the first cycle it gets 70% and the cycle II it gets 93.33%. It can be concluded that applying the VAK learning model can increase the students' motivation, creativity, and scores in social science.